Classification of Intraocular Tuberculosis. (February 2015) - Gupta, Amod; Sharma, Aman; Bansal, Reema; Sharma, Kusum
Abstract Tuberculosis in the TB endemic countries commonly manifests in the eye as tuberculous uveitis. There is a wide spectrum of the clinical manifestations of intraocular tuberculosis (IOTB). For want of any gold standard diagnostic tests or diagnostic criteria, the estimates of IOTB prevalence have varied greatly. None of the previously suggested guidelines for diagnosis of IOTB have been validated. We give definitions of clinical signs and diagnostic tests that have been used in the literature. Based on these, we propose a classification of IOTB comprising "confirmed IOTB, " "probable IOTB, " and "possible IOTB." This of necessity needs consensus among experts before carrying out studies to validate this classification.